Evaluation of Wage Incentives: Fixed Costs, Revisited. - Frank, Werner G. (The Accounting Review, 1972)
Evaluation of wage incentives in some cost accounting texts emphasizes the significance of reductions in unit fixed costs. By placing the emphasis on unit fixed cost reduction rather than on the increase in total variable contribution margins, however, students are encouraged to focus on the wrong elements of the problem. An alternative incremental approach is illustrated in this paper along with a "breakeven" variation which can be used to lessen the data requirements of the full incremental model.